Physical properties of F75 (Co-Cr-Mo Alloys) mixed with Hydroxyapatite (HAP) for Biomedical devices - A.M. Rohaya; Shamsul Baharin Jamaludin; Shaiful Rizam Shamsudin (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.